Dinoturbation in Upper Jurassic siliciclastic levels at Cabo Mondego (Lusitanian Basin, Portugal): evidences in a fluvial-dominated deltaic succession - Carvalho, Ismar de Souza (2021)
At Cabo Mondego (western central Portugal), the Upper Jurassic marine to coastal succession contains several stratigraphic levels preserving dinosaur footprints on the surface bedding plane, as well as convolute bedding and soft sediment injection structures interpreted as dinoturbation structures. At least nineteen new three-dimensional structures observed in cross-sections are interpreted as produced by dinosaur trampling. The identification of three-dimensional structures of dinosaur footprints provides an important complement to the information obtained from footprints preserved on single bedding surfaces, such as the substrate consistency, potential trackmaker identification, and the possibility to enhance the distinction of sauropods and tridactyl dinosaurs, and paleoenvironmental interpretations. In the lower part of the Arenitos da Boa Viagem Formation, eight levels of probable lowermost Kimmeridgian age (ca. 157–156 Ma), displaying the above-mentioned deformational structures, were analyzed in detail. They support interpretations concerning the relationship between the footprints and the substrate consistency at the time of their formation. Three distinct cohesiveness patterns, defined by the penetration of the feet from the paleosurface, are the result of different degrees of substrate cohesiveness. Identifying the trackmakers of levels belonging to the middle Oxfordian–lower Kimmeridgian has important implications for Late Jurassic ecosystem reconstructions, as the footprints observed in Cabo Mondego indicate a change in the morphotypes throughout the Upper Jurassic succession.